Development of a combination antibiogram for Pseudomonas aeruginosa bacteremia in an oncology population. (June 2016) - Smith, Zachary R; Tajchman, Sharla K; Dee, Brian M; Bruno, Jeffrey J; Qiao, Wei; Tverdek, Frank P
Purpose: Development of a combination antibiogram to identify combinations of antibiotics that have the highest likelihood of attaining one active agent in the empiric management of presumed Pseudomonas aeruginosa bacteremia. Methods: Patients with cancer and P. aeruginosa bacteremia from January 1 to December 31, 2012 were included in this analysis. The primary outcome was identification of effective combinations of beta-lactam and non-betalactam agents. An effective combination was defined as one which achieved in-vitro activity to greater than or equal to 85% of isolates collected. Furthermore, the addition of the non-beta-lactam agent was required to increase the in-vitro activity by at least 5% over beta-lactam monotherapy. Multiple secondary outcomes were evaluated. Results: One hundred and twenty-three P. aeruginosa isolates were included from 99 patients. Single agent beta-lactam sensitivities ranged from 72.4 to 79.7%. Combination regimen sensitivities ranged from 73.5 to 96.7%. All combination regimens that included a beta-lactam plus an aminoglycoside were found to be effective per the study definition. Independent risk factors for MDR P. aeruginosa were receipt of intravenous (IV) antibiotics within 90 days and hospital length of stay (LOS) greater than or equal to five days. Increasing the number of antibiotics received was associated with a decrease in survival to hospital discharge. Conclusions: Effective combination regimens included all beta-lactam aminoglycoside regimens. Receipt of IV antibiotics within 90 days and hospital LOS greater than or equal to five days were independent risk factors for MDR isolates.